On the Need to Review the Procedure of Official Examination of Varieties on Suitability for Dissemination in Ukraine - А. В. Андрющенко; В. М. Ткаченко (Plant Varieties Studying and Protection)
The article highlights main causes and provides reasons for changes, depending on which methodological materials on the conduct of plant varieties examination on their stability for dissemination in Ukraine should be periodically republished.